2021
DOI: 10.3389/fpsyg.2021.629376
|View full text |Cite
|
Sign up to set email alerts
|

Dealing With Negative Workplace Gossip: From the Perspective of Face

Abstract: In this study, we investigate the coping response of individuals who are being gossiped about. Drawing on face research and affective events theory, we propose that employees who are targets of negative gossip will actively respond to the gossip about them via engagement in negative gossip themselves. The findings showed that negative workplace gossip stimulated fear of losing face and led to subsequent behavioral responses, namely, engaging in negative gossip. Moreover, self-monitoring, as a moderating mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Indeed, a follow-up question could be whether this more considerable amount of negative gossip detected may be caused by brokers sending more negative gossip in the first place (or the other way around). There is evidence that individuals who are targets of negative gossip respond to it by engaging in negative gossip ( Zong et al, 2021 ). Consequently, we cannot discard the possibility of self-reinforcing dynamics: one part starts spreading negative gossip about the other, the latter learns about it and follows suit, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a follow-up question could be whether this more considerable amount of negative gossip detected may be caused by brokers sending more negative gossip in the first place (or the other way around). There is evidence that individuals who are targets of negative gossip respond to it by engaging in negative gossip ( Zong et al, 2021 ). Consequently, we cannot discard the possibility of self-reinforcing dynamics: one part starts spreading negative gossip about the other, the latter learns about it and follows suit, etc.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few years, organization researchers have shown an increasing interest in workplace gossip ( Kniffin and Wilson, 2005 ; Michelson et al, 2010 ; Mills, 2010 ; Kong, 2018 ; Kuo et al, 2018 ; Wu et al, 2018 ; Beersma et al, 2019 ; Dores Cruz et al, 2019b ; Fan and Grey, 2020 ; Lee and Barnes, 2021 ; Spoelma and Hetrick, 2021 ; Tan et al, 2021 ; Zong et al, 2021 ). One reason for this attention lies in the acknowledgment that gossip is a behavior that can have both “bright” and “dark” effects on a firm’s dynamics ( Brady et al, 2017 ; Dores Cruz et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar previous findings reported that perceived negative events from work environments intensify feelings of sadness, anger, distress, desire for revenge, unethical behavior, which subsequently stimulates deviant behaviors with others (Arain et al , 2021; Cheng et al , 2020; Guo et al , 2021; Murtaza et al , 2021; Pereira and Mohiya, 2021; Yao et al , 2020; Zhu et al , 2021). Although numerous extant studies have explored targets’ cognitive and affective reactions-related behaviors due to negative gossip (Arain et al , 2021; Babalola et al , 2019; Liu et al , 2020; Zong et al , 2021). One study (Cheng et al , 2020) used ego depletion as a cognitive reaction in the process above, which is still limited for preventing existing resources due to the devastating effects of negative gossip on this reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Targets’ hostile and negative consequences are activated after learning gossipers’ norm violation and negative talk because it is highly detrimental for reputations and impedes career advancement and development (Brady et al , 2017; Liu et al , 2020). Several recent studies argued that targets’ negative gossip detrimentally increases emotional exhaustion (Wu et al , 2018b), negative mood (Babalola et al , 2019) and anxiety (Zong et al , 2021), which, in turn, consume emotional resources. When these resources are depleted but cannot be replenished, targets may experience ego depletion (Baumeister et al , 2007; Hagger and Chatzisarantis, 2016).…”
Section: Theoretical Underpinning and Hypotheses Developmentmentioning
confidence: 99%
“…Given the abovediscussed characteristics, negative workplace gossip may trigger more detrimental consequences. Previous studies have shown that negative workplace gossip can cause great distress to the targets and have a negative impact on their work behaviors and attitudes (Ye et al, 2019;Cheng et al, 2020;Yao et al, 2020;Ullah et al, 2021;Zong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%